2019
DOI: 10.3389/fendo.2019.00219
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-A Prevents Lipopolysaccharide-Induced Neuroinflammation at the Level of the Intestinal Barrier

Abstract: In states of intestinal dysbiosis, a perturbation of the normal microbiome composition, the intestinal epithelial barrier (IEB) permeability is increased as a result of the disruption of the epithelial tight junction protein network, in which occludin is mostly affected. The loss of IEB integrity promotes endotoxemia, that is, bacterial lipopolysaccharide (LPS) translocation from the intestinal lumen to the circulatory system. This condition induces an enhancement of pro-inflammatory cytokines, which leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…Since OX1R and OX2R are expressed in the brain with some anatomical differences (Mieda and Sakurai, 2011), future work is necessary to identify brain regions or neuronal groups that are responsible for the differential metabolic effect of each orexin receptor. In addition, as orexin receptors are expressed in the peripheral tissues (Xu et al., 2013), the peripheral action of orexin may exert its effect through the maintenance of the intestinal barrier (Tunisi et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since OX1R and OX2R are expressed in the brain with some anatomical differences (Mieda and Sakurai, 2011), future work is necessary to identify brain regions or neuronal groups that are responsible for the differential metabolic effect of each orexin receptor. In addition, as orexin receptors are expressed in the peripheral tissues (Xu et al., 2013), the peripheral action of orexin may exert its effect through the maintenance of the intestinal barrier (Tunisi et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…TJs can be compromised by luminal noxious antigens, one of which is lipopolysaccharides (LPS), the main component of the outer membrane of Gram-negative bacteria. Growing investigations indicate that LPS triggers an inflammatory signaling cascade to reduce tight junction protein expression, leading to increased intestinal permeability and disrupting intestinal epithelial barrier function (He et al, 2019;Tunisi et al, 2019). Clinical study also demonstrated that circulating blood LPS levels are elevated in Crohn's disease and sepsis patients, and contribute to the pathogenesis of intestinal and systemic inflammatory response (Guo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the chronic inflammation caused by macrophage infiltration, lipopolysaccharide (LPS) plays an important role in the inflammation of adipose tissue. LPS, which is located in the outer cell membrane of Gram-negative bacteria, is released when bacteria die and is prevented from translocation into the bloodstream by the intestinal epithelium 7 . However, this protective function of the intestinal epithelium is impaired in obese animals fed with a high-fat diet.…”
mentioning
confidence: 99%